MODELLING AND OPTIMIZATION OF LOCUST BEAN POD ASH CONTENT IN ASPHALT MIXTURE USING SURFACE RESPONSE METHODOLOGY - Murana, A. A.; Ochepo, J.; Isah, A. A.; Ibedu, Kenneth Ejike (FUDMA Journal of Sciences, 2023)
Consumption of agricultural products generates large quantities of waste daily, and proper disposal mechanism is of great need. Introduction of waste pozzolanic material in asphaltic mixture creates a chemical reaction between bitumen and mineral filler as a result of its texture, geometry, chemical and mineralogical compositions. Mineral fillers play a significant role in the engineering properties of hot mix asphalt. The aim of the present study is to assess the effect of locust bean pod ash (LBPA) as mineral filler on the Marshall properties of hot mix asphalt. X-Ray fluorescence was used for characterization of LBPA, the results showed that LBPA oxide composition are comparable to that of granite dust which has been used as a conventional filler material. To accomplish this objective response surface methodology (RSM) was employed to examine the impact of LBPA on the conventional Marshall properties (Stability, Flow, VMA, Pa, VFB) of LBPA-modified asphalt mixture. By using Multi-objective process, a fifth regression model was considered with a p-value < 5% for all responses. ANOVA revealed that the LBPA had a significant effect on the Marshal properties investigated. After optimization the optimum values of LBPA and bitumen content are 40% and 50% and respectively. The predicated Marshall properties values for stability, flow, VMA, Pa and VFB are 7.639kN, 3.892mm, 18.311%, 3.63%, 78.549% respectively. The findings of this study showed that LBPA is suitable as a mineral filler in asphaltic mixture.
Keywords: Asphalt; Locust Bean Pod Ah; Marshall Properties; Optimization; Response Surface Methodology